2005
DOI: 10.1080/10428190500215100
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cyclins D1, D2 and D3 and Ki-67 in human leukemia

Abstract: Cyclins are very important components of the cell cycle machinery because their levels regulate cell proliferation. They have also been found to be prognostic factors in various cancers. We studied the expression of the positive cell cycle regulators (D cyclins) and the cell proliferation marker (Ki-67) in human acute myeloid (AML), chronic myeloid (CML), acute lymphoblastic (ALL) and chronic lymphocytic (CLL) leukemia [mainly by comparative reverse transcription polymerase chain reaction (RT-PCR)]. Both leuke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Although the majority of CLL cells from most patients express cell cycle-related markers, low percentages of Ki-67-expressing cells have been found in the blood of patients with CLL [3]. The data derived from tissue microarrays suggest that most CLL cells are in late G1 phase (cyclin Eþ) and a significant number of cells are in the S (cyclin Aþ) and G2/M phases (cyclin B1þ) of the cell cycle [4].…”
Section: Introductionmentioning
confidence: 96%
“…Although the majority of CLL cells from most patients express cell cycle-related markers, low percentages of Ki-67-expressing cells have been found in the blood of patients with CLL [3]. The data derived from tissue microarrays suggest that most CLL cells are in late G1 phase (cyclin Eþ) and a significant number of cells are in the S (cyclin Aþ) and G2/M phases (cyclin B1þ) of the cell cycle [4].…”
Section: Introductionmentioning
confidence: 96%
“…IGF1R is a tyrosine kinase regulating cell growth and survival. Considering that CCND2, CCND1, and IGFR1R are frequently up-regulated in B-CLL and diffuse large B-cell lymphoma (DLBCL) (16)(17)(18)(19)(20)(21), it makes perfect sense to find them directly targeted by miR-15b/16-2. To validate this putative targeting, we assessed all these three proteins by Western blot (WB).…”
Section: Significancementioning
confidence: 99%
“…In agreement with previous studies, [13,[19][20][21], we found over expression of cyclin D1 and Ki-67 in ALL patients. On the other hand, [22] we did not detect any elevation of cyclin D1 level among their ALL patient group (0/24).…”
Section: Discussionmentioning
confidence: 71%
“…The quantitative real time RT-PCR technique appears to be the most suitable method for that purpose [22].…”
Section: Discussionmentioning
confidence: 99%